If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 39 = 11x + -33 Reorder the terms: 39 + 3x = 11x + -33 Reorder the terms: 39 + 3x = -33 + 11x Solving 39 + 3x = -33 + 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. 39 + 3x + -11x = -33 + 11x + -11x Combine like terms: 3x + -11x = -8x 39 + -8x = -33 + 11x + -11x Combine like terms: 11x + -11x = 0 39 + -8x = -33 + 0 39 + -8x = -33 Add '-39' to each side of the equation. 39 + -39 + -8x = -33 + -39 Combine like terms: 39 + -39 = 0 0 + -8x = -33 + -39 -8x = -33 + -39 Combine like terms: -33 + -39 = -72 -8x = -72 Divide each side by '-8'. x = 9 Simplifying x = 9
| 4(x+2.49)=3x | | 5x+8=62-9x | | (x-4)(x+7)=x(2)-22 | | 2x+7=2(x-8) | | 105-6x=3x+6 | | 2x+6=21x-15 | | 0.18(y-3)+0.06y=0.14y-0.03(10) | | 8x+24=15x-70 | | 0.50x+0.10(130)=0.25(62) | | 0.70+0.20(70)=0.35(70) | | (-2)f-37=(-9) | | -3y-23=5y+17 | | 7x+3=-3+5x+16 | | 24-y=(-9) | | b^2+15b+54=0 | | 4(x+2)-8(3x+6)=9(4x+8) | | 8+-2(a+-1)=5+a | | 4*(x+2)-8*(3x+6)=9*(4x+8) | | 8-2(a-1)=5+9 | | 4x+16+40=160 | | 8-2(a-1)=7+9 | | 3+7n=31 | | 4p-10=-2p+14 | | 15-3n=9 | | 9p-7=4p+23 | | 11-2(9-1)=4+9 | | -5(x-2)=15 | | 5x+40=8x | | 5p+5=2p+20 | | -4(x-6)+7=31 | | 5*x+7=3*x+19 | | u^2-7u+6=0 |